Tuberculosis surveillance in Cape Town, South Africa: Evaluation and development of a trial protocol - Heidebrecht, Christine L (University of Ottawa (Canada), 2008)
The need to consistently evaluate surveillance systems is vital; without periodic evaluation, decisions informed by surveillance information may be based on incomplete or erroneous data. This evaluation of Cape Town's tuberculosis surveillance system was based on the CDC's Updated Guidelines for Evaluating Public Health Surveillance Systems, modified to reflect the specific context of a high burden of tuberculosis in a Middle-Income country, and emphasizing the importance of public health action that is informed by surveillance data. Findings indicate that: limitations regarding tuberculosis-human immunodeficiency virus as well as drug resistance data exist; increased availability and integration of electronic data would enhance the assessment of control efforts; and that system operations could be improved by increasing software flexibility. The development of a protocol for a trial of system changes builds upon the findings of the evaluation, and applies a logic model and an ecological health model to inform the trial design.
Keywords: Health Sciences, Public Health.; Health Sciences, Epidemiology.